The First Case Report of a Patient With Oligodendroglioma Harboring CHEK2 Germline Mutation - Li, Xueen; Xue, Hao; Luo, Ningning; Han, Tiantian; Li, Mengmeng; Jia, Deze (Frontiers in Genetics, 2022)
Introduction: CHEK2 (Checkpoint kinase 2) germline mutations were associated with elevated risk of breast cancer, colorectal cancer and other familiar cancers. Loss-of-function variants in CHEK2 are known to be pathogenic. Germline CHEK2 mutations have also been observed in medulloblastoma, primary glioblastomas. Currently, there is no direct evidence supporting the relationship of CHEK2 with central nervous system (CNS) tumors. Case presentation: A case of an oligodendroglioma patient harbored the germline CHEK2 p.R137* mutation was reported. CHEK2 p.R137* mutation occurred in forkhead-associated (FHA) domain. Given the absence of other known genetic predisposing risk factors, we considered that the oligodendroglioma might be associated with the CHEK2 mutation. The patient in our case might have a high risk of breast cancer and other multiple primary tumors. Her siblings and offspring would have 50% chance of having the same variant. Conclusions: We reported a case of an oligodendroglioma patient with family history of gastrointestinal tumors harboring germline CHEK2 pathogenic variation. This is the first report of the association between CHEK2 pathogenic variation with brain tumors that warrants further validation in larger cohorts.